2018
DOI: 10.4103/sajc.sajc_109_18
|View full text |Cite
|
Sign up to set email alerts
|

Practical consensus recommendaton for adjuvant bone-modifying agents in breast cancer

Abstract: Bone-modifying therapy is a primary research interest in breast cancer. Several features contribute to the importance of the bone environment in the management of breast cancer. Firstly, bone metastases represent the most common site of breast cancer metastases and secondly, the emergence of cancer treatment-induced bone loss (CTIBL) among breast cancer survivors and patients is of increasing concern. In the adjuvant setting, bisphosphonates can be given to prevent and treat tumor therapy-induced bone loss in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 47 publications
(60 reference statements)
0
3
0
Order By: Relevance
“…As a result of published international data, the sub-analysis of the AZURE trial and the subsequent confirmed results of the large 2015 meta -analysis [5] , [6] , [7] , [8] , [9] , [10] , [11] , adjuvant BPs have now become standard of care to reduce BC mortality in post-menopausal EBC patients in the UK as well as the rest of Europe and America, supported by published guidelines on drug choice, duration and patient selection [17] , [18] , [19] , [20] , [21] . Interestingly, a very recent study reported that extending adjuvant zoledronic acid treatment beyond 2 years did not improve the prognosis of high-risk patients with EBC receiving chemotherapy and that current recommendations for 3 – 5 years of treatment could be relaxed [25] .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As a result of published international data, the sub-analysis of the AZURE trial and the subsequent confirmed results of the large 2015 meta -analysis [5] , [6] , [7] , [8] , [9] , [10] , [11] , adjuvant BPs have now become standard of care to reduce BC mortality in post-menopausal EBC patients in the UK as well as the rest of Europe and America, supported by published guidelines on drug choice, duration and patient selection [17] , [18] , [19] , [20] , [21] . Interestingly, a very recent study reported that extending adjuvant zoledronic acid treatment beyond 2 years did not improve the prognosis of high-risk patients with EBC receiving chemotherapy and that current recommendations for 3 – 5 years of treatment could be relaxed [25] .…”
Section: Discussionmentioning
confidence: 99%
“…Following publication of the 2015 meta -analysis [11] , many international guidelines now recommend adjuvant BPs (usually intravenous zoledronic acid every six months for three years or oral clodronate) for post-menopausal women with EBC to reduce recurrence and mortality, particularly for those considered at high risk of BC recurrence [17] , [18] , [19] , [20] , [21] . Women with high risk of disease recurrence are deemed those who warrant standard adjuvant systemic chemotherapy/HER-2 targeted therapy and/or have greater that 10% 10-year risk of disease relapse.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation